Towards regenerative sustainable urbanism: The case of Curitiba and Singapore - Zingoni de Baro, Maria Elena (Curtin University, 2015)
Cities have the capabilities to transform past damage and degeneration into positive, regenerative processes. The challenge is to shift the way cities are thought about, designed and built. This thesis presents a framework for regenerative sustainable urbanism, a new approach to urban planning that combines principles of two social-ecological design perspectives that was assessed in two case studies. It is concluded that the new approach has potential in leading future urban development to regenerative sustainability processes.